STRUCTURE MODIFICATION AND MOLECULAR MODELING OF 1-(BENZOYLOXY)UREA DERIVATIVES AS ANTICANCER DRUG CANDIDATES - Suko Hardjono (UNEJ e-Proceeding)
Structure modification made in designing new drugs,by changing the structure of the lead compound.Changes in the structure of a compound would alterthe physicochemical properties including lipophilic,electronic and steric properties of the compound(Korolkovas, 1988; Siswandono, 2014). Changes inphysicochemical properties would lead to changes inthe activity of each compound (Hardjono et al,2016). Molecular modeling through in silico test is atest that is done through computer simulation.Molecular Modeling is used to predict a new drugcandidate compounds to be synthesized. This testwas performed in order to improve efficiency in theoptimization of the activity of the lead compound(Topliss J.G., 1988, Istyastoro 2007; Jenzen 2007,Kumar C.S, 2013, Dyah N.W., 2016).Some derivatives of 1-(Benzoyloxy)urea showedcytotoxic activity and predicted could be used asanti-cancer drugs (Hardjono, 2012; Hardjono 2016).Mechanism of action of urea derivatives including 1-(Benzoyloxy)urea was by inhibiting the action of theenzyme ribonucleotide reductase. This in silico testresearch done by docking the compound whicgactivities to be predicted using MVD (MolegroVirtual Docker) program. The target cell used indocking was 2EUD, a ribonucleotide reductaseenzyme crystal I, which forms a complex with thederivative 1-(Benzoyloxy)urea. 2EUD chosenbecause it was the target cell from Gemsitabin whichwork mechanism similar to urea (Xu H., 2006). Fromin silico test would be obtain Rerank Score (RS)values, which was the bond energy between theligands and target cell. Small RS value indicated thatthe bond energy needed between the compoundwith a target cell was also small. The smaller thebond energy indicated that the bond was morestable. The more stable binding of ligands to thereceptor, it could be predicted activity will be evengreater (Hardjono, 2012).In this research would be done molecular modelingof twenty-four 1-(Benzoyloxy)urea derivatives. Thein silico test result was an image that showed thehydrogen bond, Electrocic and steric interaction aswell as the value of RS from 1-(Benzoyloxy)urea andits derivatives. Of the entire RS values obtainedwould be seen 1-(Benzoyloxy)urea derivates whichhad the smallest RS value or